Cash turnover and receivables turnover to the profitability of food and beverages sector companies for the 2018-2022 period - Sapitri, Nurul Eka; Merwandani, Reivinda Putri; Hiryani, Syifa; Haryadi, Didit; Wahyudi , Wahyudi (Trigin Publisher, 2024)
Increasingly complex market dynamics and intense business competition are challenges for companies to maintain and improve their financial performance, especially in the food and beverages subsector. This study investigates the interaction between cash turnover, accounts receivables, and company profitability in Indonesia's food and beverages sector. The goal is to gain insight into how these factors interact and affect the overall profitability of a particular food and beverage company. This analysis uses quantitative methods based on financial data and relevant metrics for a sample of 17 food and beverage companies operating in Indonesia according to the variables studied. This study examines the relationship between cash turnover, receivables turnover, and profitability through statistical analysis and linear regression modeling techniques with SPSS version 26. The results showed that cash turnover significantly negatively affected profitability in food and beverages. Receivables turnover does not exert a significant effect on profitability. Cash turnover and receivables turnover also simultaneously do not have a substantial impact on profitability. The findings contribute to the existing literature on company valuations by providing empirical evidence specific to the food and beverages sector. The research has implications for policymakers, investors, and managers, as it offers valuable insights into the factors that drive a company's profitability, helping stakeholders make decisions and strategies to improve performance and competitiveness. Provide benefits in the context of financial management.